Implementasi Manajemen Strategik dalam Mengoptimalkan Pelayanan Ibadah Haji di PHU Kemenag Kota Bandung - Azzahra, Hasina; Saepuloh, Uwoh; Yuliani, Yuliani (Tadbir: Jurnal Manajemen Dakwah, 2022)
This study aims to determine the implementation of strategic management in optimizing Hajj services. This study uses a descriptive method with a qualitative approach. The results of the study indicate that the implementation of strategic management in the PHU section of the Ministry of Religion of Bandung City consists of three processes: First, the formulation of the strategy includes the formulation of the vision and mission, analysis of the internal and external environment with SWOT analysis, determination of goals and objectives, and finally the determination of strategy. Second, strategy implementation includes developing organizational culture, creating an organizational structure and providing infrastructure. Third, evaluation includes performance measurement, analysis and performance evaluation, performance and reporting on the delivery of the progress of performance results.